The evalution of aerobic and anaerobic power in decathlon - Tjouroudis, N.; Gatteschi, L.; Rubenni, M. G. (Training and care of athletes - current concepts and technologies. Fourth IOC World Congress on Sports Science, Monaco, october 22-25, 1997, Congress proceedings, 1997)
Zielstellung: Bewertung der aeroben und anaeroben Kapazität im Zehnkampf und Vergleich der Testergebnisse mit der Leistung.